In situ synthesis of HCNFs@SnS2 composite via solid-phase vulcanization reaction for high-performance anode of lithium-ion batteries - Zhang, Wenjun; Jin, Yongzhong; Zhang, Zhengquan; Chen, Ge; Jiang, Dongwei (Electrochimica acta, 2023)
•Novel HCNFs@SnS2 anode materials were first synthesized by a simple and controllable two-step method.•HCNFs@SnS2 composite exhibits the excellent reversible capacity of 901.6 mAh/g, about seven times as many as HCNFs@SnO2.•High performance of HCNFs@SnS2 benefits from the synergistic contribution between coiled carbon and SnS2 nanoparticles. Tin-based oxides or sulfides are regarded as prospective anode materials for lithium-ion batteries owing to their high theoretical specific capacity, low-cost, and low insertion/extraction potential. However, their practical application is limited duo to the poor intrinsic conductivity and tremendous volume expansion/shrinkage during Li+ intercalation/deintercalation. In this study, a simple and controllable two-step method was used to design and prepare the novel SnS2@helical carbon nanofibers (HCNFs@SnS2) anode composite, in which the size and content of SnS2 nanoparticles are about 10 nm and 62.67%, respectively. The HCNFs@SnS2 anode exhibits a superior reversible discharge specific capacity of 901.6 mAh/g (about seven times as many as HCNFs@SnO2), higher capacity retention rate of 69.1 % after 100 cycles at 200 mA/g, and an excellent ultra-long cycle capacity of 470.9 mAh/g at 2000 mA/g after 1000 cycles. The outstanding electrochemical performance of HCNFs@SnS2 mainly benefits from the synergistic contribution between HCNFs matrix and SnS2, and especially the specific 3D helical structure of HCNFs effectively improves the volumetric expansion and conductivity of SnS2 nanoparticles. This work provides some novel insights and references for developing other transition metal-oxide/sulfide-based anode materials with significantly practical application potential in energy storage areas. [Display omitted]